IN POSTER: TEACHING TRAINING AND REPRESENTATIONS OF FAMILIES ORGANIZED IN NON-CONVENTIONAL MODELS - Oliveira Júnior, Isaias Batista de (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article aimed to analyze the social representations about family among teachers who answered a Likert-type inventory in order to assess their representations about the concept of "family", "ideal family" and "unstructured family". The research data was collected during the course of a teacher training course entitled "Teacher training and representations of families organized in unconventional models by the lenses of the cinema". The results obtained revealed changes in the representations of the subjects of the research between the pre- and post-test, which are due, in part, to the fact that aesthetic experience, through the cinema, allows the rupture with the family ideals, admitting the different ways Of being family as true.